Removal and recovery of ammonia from chicken manure - ÇALLI, BARIŞ (IWA PUBLISHING, 2017)
The feasibility of the conversion of organic nitrogen available in raw chicken manure (CM) into ammonia via hydrolysis and the removal of ammonia from anaerobically digested manure were evaluated in this study. Firstly, the hydrolysis experiments were performed and the effects of temperature, total solids (TS) content and retention time were investigated. The results showed that 90% of the organic nitrogen in CM can be converted into ammonia via biological hydrolysis within 3.6 days at 35 degrees C and 10-12.5% TS content. In addition to high ammonification efficiency, partial acidification of the CM was also experienced during this period. Secondly, removal of ammonia from anaerobically digested CM was examined by flushing the head space of a vigorously stirred bottle partially filled with digestate. At 35 degrees C, after 45 hours 77% of the influent ammonia was removed.
Keywords: ammonification; biological hydrolysis; head space flushing; ANAEROBIC-DIGESTION; CO-DIGESTION; INHIBITION; WASTE; PRETREATMENT; EMISSIONS; EFFLUENT; NITROGEN; ENERGY; SLURRY